2021
DOI: 10.1111/tbj.14170
|View full text |Cite
|
Sign up to set email alerts
|

Atypical ductal hyperplasia on core needle biopsy: Surgical outcomes of 200 consecutive cases from a high‐volume breast program

Abstract: Atypical ductal hyperplasia (ADH) is an indication for excisional biopsy to rule out occult breast cancer. We analyzed pathological findings on excisional biopsy for ADH diagnosed in a high volume breast center equipped with digital tomosynthesis. Two hundred consecutive patients were diagnosed with ADH on core biopsy with radiographic concordance followed by excisional biopsy. On excisional biopsy, 33 patients (16.5%) were diagnosed with DCIS or invasive breast cancer. Patients with a concurrent diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Since the last consensus conference, several studies reported an upgrade rate of ADH into malignancy (DCIS or invasive cancer) between 7.3 and 57% in targeted OE. Consequently, the majority of these studies recommended OE, although increasingly considering other options such as imaging follow-up after VAB, when the calcifications in clinical imaging have been completely removed [6,19,[22][23][24][25][26][27][28][29][30][31]. In the MIBB database, patients with ADH underwent OE in the majority of cases (62.7%), and an upgrade rate of 25.2% was observed.…”
Section: Current Evidence For Underestimation After Cnb/vabmentioning
confidence: 99%
“…Since the last consensus conference, several studies reported an upgrade rate of ADH into malignancy (DCIS or invasive cancer) between 7.3 and 57% in targeted OE. Consequently, the majority of these studies recommended OE, although increasingly considering other options such as imaging follow-up after VAB, when the calcifications in clinical imaging have been completely removed [6,19,[22][23][24][25][26][27][28][29][30][31]. In the MIBB database, patients with ADH underwent OE in the majority of cases (62.7%), and an upgrade rate of 25.2% was observed.…”
Section: Current Evidence For Underestimation After Cnb/vabmentioning
confidence: 99%
“…Although the management of these benign and atypical lesions is controversial, they are often excised to rule out underlying malignancy that is not detected during CNB [ 3 , 4 , 28 – 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Zusammenschau der Literaturdaten der letzten Jahre ist das Unterschätzungsrisiko bei einer ADH immer noch hoch und je nach Studie liegt die Upgraderate bei 10–50 % im nachfolgenden Exzisat [ 3 , 11 , 15 , 17 , 29 , 35 , 37 , 41 , 52 ]. Risikofaktoren sind dabei die fehlende Korrelation zwischen bildgebendem Befund und Pathologie, grössere/ausgedehntere bildgebende Befunde oder Herdbefunde und die Art der Biopsie (Diagnose der ADH an Stanz- oder Vakuumbiopsie) [ 4 , 34 , 38 , 41 ].…”
Section: Atypische Duktale Hyperplasieunclassified